Platelet Concentrates From Platelet-Rich Plasma And Apheresis Machines: Biochemical Parameters, Functional Assays And Clinical Outcomes - Bahari, Mazura (2013)
The function of platelets is to form a mechanical plug to seal the site of vascular injury during hemostatic. Generally, platelet transfusion can reduce the risk of mortality. Aside from the general condition of patients, the quality of platelets to be transfused is highly important for a successful treatment. Providing patients with optimally functioning platelet concentrates (PCs) is the major concern of National Blood Center (NBC). For more than three decades, the manual method of platelet preparation has been the standard procedure in the National Blood Center (NBC) of Malaysia. However, the quality of PCs prepared through the manual and apheresis methods has yet to be investigated and compared. The quality of PCs is affected by preparation methods, types of storage bags, storage solution and storage conditions. This study aims to determine the quality and outcomes of the PCs obtained using the manual method and the automated apheresis machines; “W”, “X”, “Y” and “Z” by detecting the pH, sterility, platelet count, cytokine and platelet activation levels as well as determining the efficacy of platelet after being transfused to the patients. The quality of platelet concentrates obtained is affected by several factors such as high centrifugation forces, exposure to artificial surfaces, storage in different types of bags and different platelet preparation methods. These factors may affect the extent of platelet storage lesions and contribute to the poor clinical effectiveness and transfusion reactions of platelet concentrates.